Investigations into Corporate Capital Structure - Sun, Zhiyue (Curtin University, 2020)
This thesis investigates corporate leverage through the perspectives of measuring stability of leverage, followed by assessing stability of interest expense and the valuation implications of leverage management, and lastly the relationship between leverage management and firm default risk.